2021
DOI: 10.1097/opx.0000000000001672
|View full text |Cite
|
Sign up to set email alerts
|

Topical Review: Assessment of Binocular Sensory Processes in Low Vision

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…Low vision is defined as visual acuity worse than 6/18 and visual fields less than 20° in diameter in the better-seeing eye with the best possible correction [ 30 ]. The meaning of 6/18 is that someone with normal vision can see letters at 18 m, but a person with low vision can see letters at 6 m [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Low vision is defined as visual acuity worse than 6/18 and visual fields less than 20° in diameter in the better-seeing eye with the best possible correction [ 30 ]. The meaning of 6/18 is that someone with normal vision can see letters at 18 m, but a person with low vision can see letters at 6 m [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Residual coarse stereopsis is particularly important for the successful completion of various tasks in daily life, such as walking and grasping. Hence, patients with coarse stereopsis have a better quality of life [28] and motor skills [29] than those with poor or absent stereopsis. Absence of stereopsis increases the risk of falls [15] .…”
Section: Visual Function and Visual Rehabilitation In Cvlmentioning
confidence: 99%
“…The absence of stereopsis in patients with macular degeneration with bilateral vision impairment has been associated with reduced overall quality of life, with these patients scoring low on reading ability scores. 45 It has also been reported that reduced depth perception and stereoacuity confers a significant relative risk of multiple falls and hip fractures secondary to falls. Thus, it is not suprising that patients with residual stereopsis have better visual function and motor skills than those who lose this function completely.…”
Section: Stereopsismentioning
confidence: 99%
“…Coarse stereopsis in patients with central vision loss is important for performing tasks of daily living. The absence of stereopsis in patients with macular degeneration with bilateral vision impairment has been associated with reduced overall quality of life, with these patients scoring low on reading ability scores 45 . It has also been reported that reduced depth perception and stereoacuity confers a significant relative risk of multiple falls and hip fractures secondary to falls.…”
Section: Binocular Visual Functionmentioning
confidence: 99%